Motivation to Transfer Training and Individual Performance: the Influence of Transformative Learning and Supervisor Support - Pudjiarti, Emiliana Sri; Dwi Putranti, Honorata Ratnawati; Nurchayati, Nurchayati (Department of Management, Faculty of Economics and Business, Universitas Negeri Semarang, 2019)
This article discusses the mediating role of motivation to training transfer as mediation in the relationship between supervisor support and transformative learning on lecturer performance. Survey methods and purposive non random sampling techniques were used with the help of a questionnaire based on a 7-point Likert scale. The number of fit samples was 199 to test the hypothesis. Amos and structural models are used to test the statistical significance of the path coefficients. The findings of the study explain that supervisor support and transformative learning can encourage lecturers to make intense efforts in utilizing the skills and knowledge learned during the training process. The study also highlighted the motivation of training transfer as the key to successfully improving lecturer performance. Training plays an important role in the HRM strategy in an effort to renew the HRM competencies needed by the organization today. Therefore, motivation for training transfer is an important problem faced by professionals in developing HRM. This means that positive transfer training motivation requires that trainees can effectively apply what has been learned to the job, which leads to meaningful changes in performance.